solve both questions ..
Attachments:
![](https://hi-static.z-dn.net/files/dee/651e1cc3cb479e1dbfb30b1c8f9ea4d6.jpg)
Answers
Answered by
5
HELLO DEAR,
------------------------(1)---------------------------
given that:-
(x=3)
now put this value in the Equation
we get,
x²-x+k=0
=> 3²-3+k=0
=> 9-3+k=0
=> 6+k=0
=> k= - 6
--------------------and----------------------
given that
Equation are EQUAL roots
hence,
D=0
x²-k(2x+k+x)+p=0
=> x²-k²-3kx +p
=> x²-3kx +(p-k²)=0
a=1
b=-3k
c=(p-k²)
![d = \sqrt{ {b}^{2} - 4ac} \\ \\ d = \sqrt{ {( - 3k)}^{2} - 4 \times 1 \times (p - {k}^{2} )} = 0 \\ \\ = 9 {k}^{2} - 4p + 4 {k}^{2} = 0 \\ \\ = 9 {( - 6)}^{2} - 4p + 4 {( - 6)}^{2} = 0 \\ \\ = 324 - 4p + 144 = 0 \\ \\ = 468 = 4p \\ \\ p = \frac{468}{4} \\ \\ p = 117 d = \sqrt{ {b}^{2} - 4ac} \\ \\ d = \sqrt{ {( - 3k)}^{2} - 4 \times 1 \times (p - {k}^{2} )} = 0 \\ \\ = 9 {k}^{2} - 4p + 4 {k}^{2} = 0 \\ \\ = 9 {( - 6)}^{2} - 4p + 4 {( - 6)}^{2} = 0 \\ \\ = 324 - 4p + 144 = 0 \\ \\ = 468 = 4p \\ \\ p = \frac{468}{4} \\ \\ p = 117](https://tex.z-dn.net/?f=d+%3D+%5Csqrt%7B+%7Bb%7D%5E%7B2%7D+-+4ac%7D+%5C%5C+%5C%5C+d+%3D+%5Csqrt%7B+%7B%28+-+3k%29%7D%5E%7B2%7D+-+4+%5Ctimes+1+%5Ctimes+%28p+-+%7Bk%7D%5E%7B2%7D+%29%7D+%3D+0+%5C%5C+%5C%5C+%3D+9+%7Bk%7D%5E%7B2%7D+-+4p+%2B+4+%7Bk%7D%5E%7B2%7D+%3D+0+%5C%5C+%5C%5C+%3D+9+%7B%28+-+6%29%7D%5E%7B2%7D+-+4p+%2B+4+%7B%28+-+6%29%7D%5E%7B2%7D+%3D+0+%5C%5C+%5C%5C+%3D+324+-+4p+%2B+144+%3D+0+%5C%5C+%5C%5C+%3D+468+%3D+4p+%5C%5C+%5C%5C+p+%3D+%5Cfrac%7B468%7D%7B4%7D+%5C%5C+%5C%5C+p+%3D+117)
-------------(2)--------------
let the no. are x,(x+1),(x+2)
according to question
x²+(x+1)(x+2)=46
=> x²+x²+2x+x+2=46
=> 2x²+3x-44=0
=> 2x²+11x-8x-44=0
=> x(2x-11) -4(2x-11)=0
=> (x-4)(2x-11)=0
=> x=4
----------------or--------------------
x=11/2
hence,the other no. will be,
[ 4 , 5 , 6 ]
I HOPE ITS HELP YOU DEAR,
THANKS
------------------------(1)---------------------------
given that:-
(x=3)
now put this value in the Equation
we get,
x²-x+k=0
=> 3²-3+k=0
=> 9-3+k=0
=> 6+k=0
=> k= - 6
--------------------and----------------------
given that
Equation are EQUAL roots
hence,
D=0
x²-k(2x+k+x)+p=0
=> x²-k²-3kx +p
=> x²-3kx +(p-k²)=0
a=1
b=-3k
c=(p-k²)
-------------(2)--------------
let the no. are x,(x+1),(x+2)
according to question
x²+(x+1)(x+2)=46
=> x²+x²+2x+x+2=46
=> 2x²+3x-44=0
=> 2x²+11x-8x-44=0
=> x(2x-11) -4(2x-11)=0
=> (x-4)(2x-11)=0
=> x=4
----------------or--------------------
x=11/2
hence,the other no. will be,
[ 4 , 5 , 6 ]
I HOPE ITS HELP YOU DEAR,
THANKS
Answered by
4
Answer:
(1)
2
+(1)−2=0
so(x−1)isazeroofthispolynomial∣becausex−1=0sox=1∣
similarly(x+2)isalsoazero
let(x+1)beaand(x+2)beβ
so
x−1
1
−
x+2
1
=
(x−1)(x+2)
x+2−(x−1)
=
(x−1)(x+2)
3
(2)--------------
let the no. are x,(x+1),(x+2)
according to question
x²+(x+1)(x+2)=46
=> x²+x²+2x+x+2=46
=> 2x²+3x-44=0
=> 2x²+11x-8x-44=0
=> x(2x-11) -4(2x-11)=0
=> (x-4)(2x-11)=0
=> x=4
----------------or--------------------
x=11/2
hence,the other no. will be,
[ 4 , 5 , 6 ]
hope it help u
Similar questions
Hindi,
9 months ago
Math,
9 months ago
English,
9 months ago
Social Sciences,
1 year ago
History,
1 year ago